ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN DI DESA SULAHO KECAMATAN LASUSUA KABUPATEN KOLAKA UTARA - hamid, ahmad; Ilham Akbar Garusu (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
Accounting is an art to record, classify, and add up the value of transactions that have been carried out by the company as part of Financial Accountability presented in a systematic form. This study was conducted with the aim to determine the application of environmental accounting in Sulaho Village, Lasusua District, Kolaka Utaras Regency using secondary data and interviews. The results obtained that mining companies in identifying the costs incurred for the waste management process has not been maximized because these costs are still combined with allied costs, such as transportation costs and destruction costs for solid waste included in the expenditure of goods and services included in the partnership program, for liquid waste costs such as maintenance costs and employee salaries included in the expenditure of goods and services. Mining companies in measuring the costs associated with the waste management process refers to the realization of previous costs and the amount of costs required and the realization of the budget incurred is not much different. Mining companies make recognition of accounting transactions by the accrual basis method. Mine management in presenting the costs associated with the waste management process the hospital presents it in the general financial statements, the hospital does not present the costs associated with the waste management process into special financial statements. Mining companies in their disclosures for waste management costs are included in the Notes to the Financial Statements. Environmental costs in particular costs incurred related to waste management are treated as costs of employee salaries and expenditure on goods and services.